Some methodological challenges of designing LSP courses - Sowa, Magdalena (Glottodidactica, 2019)
The aim of the text is to discuss issues related to planning LSP courses. The key stages of course design are understandable and clear to most LSP teachers. However, their practical implementation can raise certain doubts or questions. The paper attempts to analyse such problematic aspects of LSP course planning in detail. We will situate these problems at particular stages during course design and show to what extent they can affect the success of LSP education. In our opinion, the diagnosis and analysis of these sensitive areas can be helpful not only in the effective planning of LSP training programmes but also in language teachers’ education for professional purposes.